The Effect of Operational Audit and Internal Control on Service Effectiveness at Puskesmas Dramaga - Hurriyaturrohman, Hurriyaturrohman; Lestari, Putri; Sundarta, M. Imam; Yudiana, Yudiana (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
This study aims to determine (1) the effect of operational audit on service effectiveness at Dramaga Community Health Center, (2) the effect of internal control on service effectiveness at Dramaga Community Health Center, (3) the effect of operational audit and internal control on service effectiveness at Dramaga Community Health Center. This research adopts a quantitative approach with service effectiveness as the dependent variable, while operational audit and internal control are the independent variables. Data collection in this study involves primary data by distributing questionnaires to the targeted subjects as respondents. The study employs a total sampling method, where all employees of Dramaga Community Health Center are taken as samples, totaling 31 respondents. Hypotheses are tested using multiple linear regression method with the assistance of statistical tool, SPSS version 26. The results of the study indicate that operational audit partially and significantly influences service effectiveness, internal control partially and significantly affects service effectiveness, and both operational audit and internal control simultaneously influence service effectiveness. It can be concluded that the better the implementation of operational audit in the community health center, the better the service effectiveness provided. Similarly, internal control, where the enhancement of internal control quality in the community health center significantly contributes to the improvement of service effectiveness. Thus, the findings of this study affirm the importance of implementing operational audit and internal control to enhance service quality in community health center